A CTI System to Support the Seamless Workplace and Its Implementation. Issue 2 (July 2014) - Watanabe, Toru; Koizumi, Hisao
SUMMARY This paper proposes a CTI client/server coordination system exclusively for use with a smart phone. The system makes use of a CTI client, performing combined functions of a SIP phone and a Web browser. The proposed CTI client/server coordination system comprises SIP servers and Web servers, both of which are installed in enterprises, and CTI clients that run on smart phones in a mobile environment. Furthermore, the CTI clients perform the function of SIP phone by communicating with SIP servers. In addition, CTI clients can display telephone directories and logging of phone calls stored in Web servers. They can display screens of ordinary Web browsers. Here, one might switch between a SIP phone function and a Web communication screen with merely a single touch of the tab key. Consequently, smart phones in the mobile environment make it possible to conduct telephone meetings while browsing with a Web screen.